Bahan Bakar Padat Dari Tandan Kosong Sawit Menggunakan Proses Torefaksi Dengan Variasi Suhu Dan Waktu Torefaksi - Zen, Muhammad; Helwani, Zuchra; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Empty fruit bunches (EFB) can be used as alternative energy source by using torrefaction process. Torrefaction is a pre-treatment process of biomass into solid fuel within temperature range of 200-300oC in an inert condition. The Torrefaction process research aims to produce solid fuel from EFB and study the effect of process variabel towards characteristic of solid fuel resulted. Torrefaction of empty fruit bunch was using fixed bed horizontal reactor with temperature (250-300oC) and torrefaction time (15-45 minute). Product quality resulted was calorific value, mass yield, energy yield and proximate (moisture content, ash content, volatile content and fixed carbon). The result obtained for calorific value in range was 19883.03-23165.96 kJ/kg, mass yield was 47.93-71.64 %, and energy yield was 65.09-86.39 %. 17091.03-20697.13 kJ/kg, mass yield was 35.95-59.91 %, and energy yield was 50.97-72.91 %. Proximate analysis resulted in the form of moisture content was 0.40-0.73 %, ash content was 8.75-10.16 %, volatile content was 35.94-64.48 %, and fixed carbon was 26.78-53.90 %. From the result obtained, the effect of rising temperature and torrefaction time give linier effects toward the product quality. Increased temperature and torrefaction time give enhancement to the calorific value, ash content, and fixed carbon.Keywords: biomass, empty fruit bunches, solid fuel, torrefaction.